2020
DOI: 10.2147/hmer.s254195
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Oral Administration of <em>Weissella confusa</em> on Fecal and Plasma Ethanol Concentrations, Lipids and Glucose Metabolism in Wistar Rats Fed High Fructose and Fat Diet</p>

Abstract: Background and Purpose: In previous investigations, Weissella confusa was shown to lack the metabolic pathway from fructose to mannitol and to produce ethanol when cultivated in the presence of fructose. Hence, we assessed the effect of oral administration of W. confusa (strain NRRL-B-14171) on blood and fecal ethanol concentrations, glucose and lipid metabolism and traits of the metabolic syndrome in Wistar rats (n=27) fed diets with two different fat and fructose levels and with or without the addition of W.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Barnesiella has close contact with immune cells and exerts anti-inflammatory protection [ 60 ]. Weissella may convert glucose and fructose directly into ethanol in the rat intestine, increasing ethanol production [ 61 ]. It results in hyperlipidemia and may promote the development of NAFLD [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnesiella has close contact with immune cells and exerts anti-inflammatory protection [ 60 ]. Weissella may convert glucose and fructose directly into ethanol in the rat intestine, increasing ethanol production [ 61 ]. It results in hyperlipidemia and may promote the development of NAFLD [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weissella may convert glucose and fructose directly into ethanol in the rat intestine, increasing ethanol production [ 61 ]. It results in hyperlipidemia and may promote the development of NAFLD [ 61 ]. Pediococcus is a probiotic that improves NAFLD by modulating gut microbiome and inflammatory responses [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have been isolated from various fermented foods, such as yoghurt, sourdough, and kimchi ( Wang et al, 2011 ; Zannini et al, 2018 ; Mun and Chang, 2020 ; Valerio et al, 2020 ), and play important roles in the process of fermentation, thereby influencing the texture and taste of foods. They also exist in the guts of humans and vertebrate animals, such as giant pandas and rainbow trout ( Xiong et al, 2019 ; Mortezaei et al, 2020 ; Wang et al, 2020 ), their functions involve reducing depressive-like behavior ( Sandes et al, 2020 ), influencing gut permeability and intestinal epithelial regeneration ( Prado et al, 2020 ), killing harmful bacteria ( Dey and Kang, 2020 ; Lee et al, 2020 ; Pelyuntha et al, 2020 ), affecting host metabolism ( Elshaghabee et al, 2020 ), and preventing cancer cell proliferation ( Le et al, 2020 ). Some Weissella species may be beneficial to plants because they inhibit the infection of plant pathogenic fungi, such as Fusarium verticillioides ( Quattrini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal microbiota influences the metabolism of the host metabolism; they regulate the immune system, digestion, absorption, and synthesis. Several studies have revealed that dysbiosis of the intestinal microbiota, which is an imbalance of microbial communities, disrupts the host's energy metabolism, and contributes to obesity and metabolic syndrome (16,17). Dietary habits and nutrition are very influential in maintaining intestinal health and can be useful or toxic to the host.…”
Section: Discussionmentioning
confidence: 99%